Pengaruh Analisis Jabatan dan Pengembangan Karir Terhadap Kinerja Pegawai Melalui Motivasi Kerja Pegawai - Nuryanti, Ai; Indaryani, Mamik Indaryani; Sutono, Sutono (Universitas Islam Nahdlatul Ulama Jepara, 2025)
This study aims to analyze the influence of job analysis and career development on employee performance through work motivation as an intervening variable. The research population consists of employees from the Department of Education, Youth, and Sports of Jepara Regency. The sampling technique used was purposive sampling, involving 168 employees. Data analysis was conducted using Structural Equation Modelling (SEM) with the assistance of AMOS software version 24. The results show that job analysis and career development have a positive and significant influence on work motivation. Additionally, job analysis and career development also significantly affect employee performance. Furthermore, job analysis and career development influence employee performance through work motivation as an intervening variable.